Green ethics and philosophy an A-to-Z guide - Newman, Julie (Thousand Oaks, Calif. London SAGE, 2011)
This volume includes topics from the Hannover Principle to green eco-feminism, responsible eco-tourism, corporate values and sustainability, and more, explained by respected experts in the field.
Includes bibliographical references and index.
Keywords: Environmental ethics; Human ecology -- Philosophy; Electronic books